The Roles of Bank Indonesia and Financial Services Authority as Rural Banks’ Supervision Agency - Dikha Anugrah; Anthon Fathanudien; Teten Tendiyanto (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
Banks are financial institutions to collect and distribute funds to the public. As a public trust institution, the banks must maintain the public trust. In doing so, it is needed a supervision agency called Bank Indonesia. The purpose of this study is to see and to analyze the roles and the responsibilities of Bank Indonesia as rural banks’ supervisory agency based on law No. 3 of 2004, Bank Indonesia and Act No. 21 of 2011, financial services authority. The writer employed a normative juridical approach by understanding, testing, and reviewing the secondary data. This research was a descriptive analysis describing the prevailing laws and regulations related to the authority of Bank Indonesia as a rural bank’s supervision agency. The result of the research showed the roles of of Bank Indonesia and Financial Services Authority as rural bank supervisors were not aligned with the law provisions stipulated in Bank Indonesia article 27, a direct and indirect supervisions. Meanwhile, based on Article 28 of Law No. 21 of 2011, Financial Services Authority. The role of the Financial Services Authority in the legal protection of the consumer was not limited to facilitating the consumer protection. For instances, it is not only to accomodating and becoming a mediation institution but also becoming an institution that sides the consumers and society in the legal defense activities. As the central bank, bank indonesia is responsible for the case happening in Rural banks by putting it under a special supervision bank. In addition, if the rural bank is unable to improve its financial condition within a specified time, it will be declared as a failed bank and its business license will be revoked. The forms of protection, on the other hand, undertaken by the Financial Services Authority covers the prevention protection of violation and restoration of consumer rights if for instance the consumers suffer losses.Bank merupakan lembaga keuangan yang menghimpun dan menyalurkan dana ke masyarakat. Sebagai lembaga kepercayaan masyarakat, bank harus dapat menjaga kepercayaan masyarakat, untuk menjaganya maka diperlukan badan pengawasan yaitu Bank Indonesia. Tujuan penelitian ini untuk mengetahui dan menganalisis peranan dan tanggung jawab Bank Indonesia sebagai badan pengawas terhadap Bank Perkreditan Rakyat berdasarkan Undang-Undang No 3 Tahun 2004 Tentang Bank Indonesia dan Undang-undang no 21 Tahun 2011 tentang Otoritas Jasa Keuangan. Metode pendekatan yang digunakan oleh penulis adalah metode pendekatan yuridis normatif dengan memahami, menguji, dan mengkaji data sekunder. Penelitian ini bersifat deskritif analisis, menggambarkan peraturan perundang-undangan yang berlaku dan berkaitan dengan Bank Indonesia terhadap kewenangannya sebagai badan pengawas kepada Bank Perkreditan Rakyat. Hasil penelitian adalah Peranan Bank Indonesia dan Otoritas Jasa Keuangan sebagai pengawas dan pembina terhadap Bank Perkreditan  Rakyat  belum  sesuai dengan yang ditetapakan Undang-Undang Bank Indonesia Pasal 27 yaitu mengenai  pengawasan   langsung    dan   pengawasn   tidak langsung. Sementara berdasarkan Pasal 28 Undang-Undang No. 21 Tahun 2011 tentang Otoritas Jasa Keuangan, Otoritas Jasa Keuangan peran Otoritas Jasa Keuangan dalam sistem hukum perlindungan konsumen tidak terbatas hanya dengan memfasilitasi perlindungan konsumen yakni menampung dan menjadi lembaga mediasi tetapi juga menjadi lembaga yang berpihak kepada konsumen dan masyarakat dalam bentuk kegiatan pembelaan hukum.  Bank  Indonesia  sebgai  Bank  sentral  bertanggung  jawab  terhadap kasus  Bank Perkreditan Rakyat  dengan  memasukkan  bank tersebut   ke dalam Bank Dalam Pengawasan Khusus. Pada waktu yang   telah  ditentukan   Bank Perkreditan Rakyat   tidak  dapat   memperbaiki  kondisi keuangannya.  Bank Perkreditan Rakyat  dinyatakan  sebagai bank   gagal   dan    dicabut   ijin   usahanya. Sementara Bentuk-bentuk perlindungan yang dilakukan oleh Otoritas Jasa Keuangan meliputi perlindungan dalam upaya pencegahan terjadinya pelanggaran dan pemulihan hak-hak konsumen apabila konsumen mengalami kerugian.